La part manquante du paysage - Valentine Losseau (Projets de Paysage)
In the forest of Chiapas a landscape is being built, wich paradoxically emphasizes the tropical wilderness as a touristic product for the new market developped by the mexican government and NGOs. Landscaping is therfore more focused on the enhancement of an illusory wild forest than on the environmental integrity of a threatened ecosystem ; and show up central concepts of scientific ecology. In turn, the Lacandon Mayas who live in the forest transform their territory in a reflexive relationship...two cosmological, aestethical, cultural prisms are crossing the forest and redesigning its landscapes. How the « missing part of landscape » ( deforestation, extinct biodiversity etc.) is designed in land settlement on both sides of this interface situation between indigenous villagers and forest managers ?